2007
DOI: 10.1016/j.mrgentox.2006.09.010
|View full text |Cite
|
Sign up to set email alerts
|

Perturbation of cytochrome P450, generation of oxidative stress and induction of DNA damage in Cyprinus carpio exposed in situ to potable surface water

Abstract: Epidemiological evidence suggests a link between consumption of chlorinated drinking water and various cancers. Chlorination of water rich in organic chemicals produces carcinogenic organochlorine by-products (OBPs) such as trihalomethanes and haloacetic acids. Since the discovery of the first OBP in the 1970s, there have been several investigations designed to determine the biological effects of single chemicals or small artificial OBP combinations. However, there is still insufficient information regarding t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
18
0
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 50 publications
(56 reference statements)
5
18
0
1
Order By: Relevance
“…The positive mutagenic effect here detected by the MN induction in fish erythrocytes confirms those previously presented by Sapone et al [32]. They are also in agreement with results obtained from the longitudinal study on the genotoxic effect (Comet assay and MN test) induced by disinfectants in fish erythrocytes of C. carpio [54] which showed a clear genotoxic effect mainly induced by NaClO and to a lesser extent by ClO 2 , as opposed to the negative results obtained from PAA.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The positive mutagenic effect here detected by the MN induction in fish erythrocytes confirms those previously presented by Sapone et al [32]. They are also in agreement with results obtained from the longitudinal study on the genotoxic effect (Comet assay and MN test) induced by disinfectants in fish erythrocytes of C. carpio [54] which showed a clear genotoxic effect mainly induced by NaClO and to a lesser extent by ClO 2 , as opposed to the negative results obtained from PAA.…”
Section: Discussionsupporting
confidence: 92%
“…A similar heterogeneous pattern of induction/suppression of phase I MFO modulation was also shown in a previous pilot experiment carried out in autumn (October) [32]. It was reported that the most induced CYP isoforms were CYP1A1 and CYP2B1, in particular with PAA and NaClO disinfectants after 10 days' treatment while the most notable inactivation regarded CYP2E1 activity by ClO 2 in both time periods.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…These findings were confirmed by the areas obtained in IBR star plots. In contrast to these results, depletion of CYP 2E1-like activity has been reported to occur in common carp (Cyprinus carpio) exposed to HM precursors, such as NaClO and ClO 2 (Sapone et al 2007). These differences are probably explained by oxidative damage induced by residual chlorine, although some part of the content of these chemicals may have formed HMs depending on temperature, pH, and the presence of organic carbon.…”
Section: Biomarkers Of Exposure and Hm-induced Damagementioning
confidence: 61%
“…There is little information regarding toxicity in fish induced by HMs and haloacids, which are potentially carcinogenic compounds (Teuschler et al 2000;Sapone et al 2007). In the present study, formaldehyde, a major metabolite of chlorinated or chlorobrominated HMs, was detected in both organ tissues, but its levels were greater in liver.…”
Section: Biomarkers Of Exposure and Hm-induced Damagementioning
confidence: 99%